2019
DOI: 10.1080/16549716.2019.1639388
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Drug Bag’ method: lessons from anthropological studies of antibiotic use in Africa and South-East Asia

Abstract: Understanding the prevalence and types of antibiotics used in a given human and/or animal population is important for informing stewardship strategies. Methods used to capture such data often rely on verbal elicitation of reported use that tend to assume shared medical terminology. Studies have shown the category ‘antibiotic’ does not translate well linguistically or conceptually, which limits the accuracy of these reports. This article presents a ‘Drug Bag’ method to study antibiotic use (ABU) in households a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…The final obvious key limitation of the study is that we relied on self-reported responses, which are inevitably prone to respondent recall bias and social desirability bias. Obtaining more objective data in such surveys and contexts is very difficult, but future work could test possible methodological innovations [70].…”
Section: Discussionmentioning
confidence: 99%
“…The final obvious key limitation of the study is that we relied on self-reported responses, which are inevitably prone to respondent recall bias and social desirability bias. Obtaining more objective data in such surveys and contexts is very difficult, but future work could test possible methodological innovations [70].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in the social sciences remind us of the dangers of injecting subjective bias and unfair judgement into scientific debate [ 19 , 20 ]. Anthropological studies of antibiotic use in Sub-Saharan Africa and South-East Asia used the ‘drug bag’ method to address conceptual and semantic issues [ 21 ]. By ‘appropriate’ use we mean that if a medicine is used appropriately (in a clinical sense) it is safe and effective in treating the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Details of this method have been described elsewhere. 39 The second phase is longitudinal ethnographic fieldwork, including participant observation and key informant interviews with residents, medicine retailers (pharmacists, drug shop workers and market vendors) and healthcare workers in clinics and hospitals. With prescribers and retailers, qualitative methods are complemented and contextualised by the collection of quantitative data about antimicrobial prescription, stocks and sales.…”
Section: Recruitment Data and Sample Collection For Control Participmentioning
confidence: 99%